Weekly docetaxel with or without gemcitabine as second-line chemotherapy in paclitaxel-pretreated patients with metastatic breast cancer: A randomized phase II study conducted by the hellenic co-operative oncology group - Papadimitriou, C.A.; Kalofonos, H.; Zagouri, F.; Papakostas, P.; Bozas, G.; Makatsoris, T.; Dimopoulos, M.-A.; Fountzilas, G. (Oncology, 2009)
Objective: A randomized phase II trial was conducted to test whether the addition of gemcitabine to weekly docetaxel could improve the objective response rate and survival outcomes as second-line chemotherapy in patients with metastatic breast cancer who have failed a paclitaxel-containing regimen. Methods: Patients were randomized to receive either weekly docetaxel 40 mg/m2 (group A, n = 34) or the combination of weekly docetaxel 35 mg/m2 with gemcitabine 600 mg/m2 (group B, n = 41). Three consecutive weekly infusions followed by a 1-week rest period represented 1 chemotherapy cycle. Results: The objective response rate was 18% and 27.5% in group A and B, respectively (p = 0.413). No statistically significant differences were demonstrated in terms of median overall survival and time to disease progression. The rate and grade 3 and 4 neutropenia were higher in group B (23 vs. 3%). Conclusions: The weekly administration of docetaxel and gemcitabine did not result in superior clinical outcomes over weekly docetaxel. © 2009 S. Karger AG, Basel.
Keywords: Docetaxel; Gemcitabine; Metastatic breast cancer; Second-line chemotherapy